A Re-Thinking of Uka Di N’obi Gender Phenomenon: A Present Deterrent to The Growth of Christianity in Igboland - Omeike , Cornelius A. (African Journal of Education,Science and Technology (AJEST), 2017)
Uka di n’obi literally means that ‘divine worship is subjective, personal, and should not be influenced by any public orthodox regulations’. It betrays a complex of laissez-faire attitude in one’s personal commitment towards divine worship. It encourages one to isolate one’s self from a common congregational worship for the purpose of maximizing leisure. This attitude readily develops into a large scale religious apathy. A close survey of people’s religious piety and praxis tend to apportion higher marks to the women-folk than to the men-folk in Igboland. More of the female-folk attend religious gatherings, promote prayerful exercises, and resort to God at difficult moments. It is not a question of number or emotion but a question of interest and a conscious self-commitment. On explicit self-commitment, Karl Rahner introduced the concept of “anonymous Christianity”. When applied to them, they unambiguously promote God and expect to attain salvation through the explicitly constituted Christianity but at their pace. Once their salvation is assured by their ‘anonymity’, they do border to question their partial or total commitment to Christianity. But what is the fate of the Christian church if every member adopts anonymity? In how far does the anonymity assure members of the desired salvation? While this paper frowns at anonymity, it devices every means to include as it invites indifferent Christians to the task of active membership. It specifically outlines the reasons th